AN INSTITUTIONAL ANALYSIS OF INTEGRATED RIVER BASIN MANAGEMENT: THE CASE OF KEDUANG AND KETONGGO RIVERS IN THE BENGAWAN SOLO SUB BASIN, INDONESIA - , NURUL HASANA SOFYANTHI AWUY, Ir. Leksono Probo Subanu, MURP.,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Integrated river basin approaches are indispensable in order to prevent problems and conflicts and to meet social and natural demands. River basin is a complex system which is bordered by hydrological and not political boundaries. Therefore, integrated river basin management can be defined as a process of coordinating conservation, management, and development of water, land, and related resources across political sectors within a given river basin, in order to maximize the economic and social benefit derived from water resources in an equitable manner while preserving and, where necessary, restoring fresh water ecosystems. The integration of river basin management can be also explained as an effective social network among its stakeholders. Social network theory is important to understand integrated river basin management, especially on the relationship among stakeholders. These partnerships offer an institutional forum in which multiple policy stakeholders in discussing and negotiating river basin management plans. The integrated river basin management is successful to increase the communication and coordination and exchange of information among stakeholders, build a forum to accommodate various interests and views. On the other hand, the traditional river basin management showed less communication and coordination and exchange information among stakeholders. There, the forum of information sharing and communication and conflict resolution among stakeholders did not exist. When we compare the institutional performance results between those two river basins management, there is a significant difference about the use of land of river basin area. The integrated river basin management succeeds to conserve the forest area. The increase of peopleâs awareness and willingness about environment consideration contributed to the stable of forest area. However, the traditional river basin management indicated an ineffective performance based on ecology purpose because the forest area decreased lost. The peopleâs awareness and willingness to conserve the river basin area is lower than the integrated river basin management area.